Electron Holography: Correlative High‐Resolution Mapping of Strain and Charge Density in a Strained Piezoelectric Multilayer (Adv. Mater. Interfaces 1/2015). Issue 1 (January 2015) - Song, Kyung; Koch, Christoph T.; Lee, Ja Kyung; Kim, Dong Yeong; Kim, Jong Kyu; Parvizi, Amin; Jung, Woo Young; Park, Chan Gyung; Jeong, Hyeok Jae; Kim, Hyoung Seop; Cao, Ye; Yang, Tiannan; et al.
<x xml:space="preserve">Abstract</x> Sub‐nanometer resolution 2D strain maps of the InGaN/GaN multiquantum wells in conventional blue light emitting diodes reveal that the InGaN quantum wells are compressively strained and elongated along the polar growth direction, exerting compressive stress/strain on the GaN quantum barriers. In article 1400281, S. H. Oh and co‐workers demonstrate that a combined analysis of the strain maps with the total charge density map quantitatively evaluates the internal piezoelectric fields and the electrostatic screening interaction between the polarization charges and the free charge carriers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>